2011
DOI: 10.1002/jmv.22017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors and virological profile of chronic hepatitis b virus infection in pregnant women in India

Abstract: A large program was conducted by the Government of India to study the prevalence and profile of chronic hepatitis B virus (HBV) infection and its risk factors in pregnant women attending a tertiary care hospital in India. From September 2004 to December 2008 consecutive pregnant women attending the antenatal clinic were screened and those found positive for HBsAg were enrolled. Healthy non-pregnant women of child-bearing age, who presented for blood donation during the same period, served as controls. Women wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 22 publications
3
48
0
Order By: Relevance
“…[49][50][51][52] A large study involving 8575 pregnant women from Northern India, documented HBsAg carrier rate in antenatal mothers to be 3.7%, HBeAg carrier rate 7.8% and vertical transmission was observed in 18.6%. 53 However, a recent study by Dwivedi et al 54 has shown a lower prevalence rate of 0.9%.…”
Section: Pregnant Womenmentioning
confidence: 99%
“…[49][50][51][52] A large study involving 8575 pregnant women from Northern India, documented HBsAg carrier rate in antenatal mothers to be 3.7%, HBeAg carrier rate 7.8% and vertical transmission was observed in 18.6%. 53 However, a recent study by Dwivedi et al 54 has shown a lower prevalence rate of 0.9%.…”
Section: Pregnant Womenmentioning
confidence: 99%
“…5 In India, the prevalence rate of HBsAg positivity in pregnant women in studies before 1990s varies from 2.6 to 9.5%, [6][7][8][9][10][11] whereas more recent studies have reported HBsAg positivity among pregnant women ranging from 0.8 to 1.1%. [12][13][14] The HBeAg positivity among HBsAg positive pregnant women have varied widely from 4.8% to 68.7%. 6,14 In a recent study from Delhi, which found HBsAg prevalence of 1.1% among pregnant women, it was found that the alanine aminotransferase (ALT) levels were normal in 54% of the women and HBV DNA levels were above 10,000 copies/mL (2000 IU/ml) in 71% of women.…”
Section: Prevalence Of Chronic Hepatitis B Virus Infection Among Pregmentioning
confidence: 99%
“…[12][13][14] The HBeAg positivity among HBsAg positive pregnant women have varied widely from 4.8% to 68.7%. 6,14 In a recent study from Delhi, which found HBsAg prevalence of 1.1% among pregnant women, it was found that the alanine aminotransferase (ALT) levels were normal in 54% of the women and HBV DNA levels were above 10,000 copies/mL (2000 IU/ml) in 71% of women. The median HBV DNA levels were higher inHBeAg-negative group.…”
Section: Prevalence Of Chronic Hepatitis B Virus Infection Among Pregmentioning
confidence: 99%
“…Other studies demonstrate that percentages of HBsAgs were 0.9%, 16% and 84% due to tattooing in 78.4% [7]. Other study showed that 1.1% of healthy non pregnant women were positive for HBsAgs and ALT level were elevated in 54% of those women and HBV DNA levels were above 2000 IU/ml in 71% of women and had a higher risk of transmission infection to their newborn [8]. HBsAgs traced in 0.5% of pregnant women in other study [9].…”
Section: Discussionmentioning
confidence: 95%